Geo i-store: the enhancement for geomatics instruments application / Zailin Mohd Asri, Noorfatekah Talib and Nur Afiqah Alias - Mohd Asri, Zailin; Talib, Noorfatekah; Alias, Nur Afiqah (College of Built Environment, 2023)
A mobile artifact not only overturns the mobile industry's traditional business model but also creates new avenues of mobile market opportunities.